Porous Co3O4@TiO2 core-shell nanofibers as advanced anodes for lithium ion batteries - Tong, Xiaoling; Zeng, Min; Li, Jing; Liu, Zhanjun (Journal of alloys and compounds, 2017)
Metal oxide materials possess splendid application prospect in lithium ions battery. In this work, one-dimensional porous Co3O4@TiO2 core-shell nanofibers (Co3O4@TiO2 CSNFs) electrode material is synthesized via a convenient hydrothermal method combined with hydrolysis method. This novel structure with sufficient available space would buffer the volume variation of Co3O4 and facilitate the mobility of Li+ during cycling, which endows Co3O4@TiO2 CSNFs with excellent electrochemical performances, such as good cyclability (632 mAh g−1 at 0.2 C and 525 mAh g−1 at 0.5 C after 100 cycles) and superior rate performance (∼359 mAh g−1 at 2 C). •Co3O4@TiO2 has been synthesized via a simple method.•Co3O4@TiO2 possesses one-dimensional porous core-shell nanofibers structure.•This novel structure endows Co3O4@TiO2 with excellent electrochemical performances.